MULLA SADRA'S THOUGHTS AND SOLUTIONS ABOUT THE PROBLEM OF EVIL - Abdullah HosseiniEskandian , Masoumeh RajabNezhadian (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
The problem of evil is one of the cases that has always been discussed by various thinkers throughout history and has attracted their attention, and this is due to its complex nature and on the other hand its conflict with the divine attributes as well as the good system.In his works, especially Asfar Arbaeh, which is his most important work of Mulla Sadra,he has paid special attention to the problem of evil.According to Mulla Sadra, evil is the lack of the essence of a thing or the lack of perfection and it is non-existent.Examining the nature of evil in Mulla Sadra's thought and explaining its relationship with the divine attributes and system of this world and expressing the types and solutions of evil is something that can make us more familiar with evil in Mulla Sadra's system of thought as one of the greatest Islamic philosopher.In this article, with a descriptive-analytical method and citing library sources, an attempt is made to comprehensively study the nature of evil in Mulla Sadra's intellectual system, and the most important attention is to Asfar Arbaeh as his most important work.Mulla Sadra considers evil as a requirement of the good system of this world, which in a minimal sense is a requirement of the nature of this world, and by using it well, many charities can be obtained.